Influence of surface morphology on erosion of plasma-facing components in H-mode plasmas of ASDEX Upgrade - A. Lahtinen; A. Hakola; J. Likonen; M. Balden; K. Krieger; S. Gouasmia; I. Bogdanovic Radovic; G. Provatas; M. Kelemen; S. Markelj; M. Pedroni; A. Uccello; et al. (Nuclear Materials and Energy, 2022)
Net erosion of plasma-facing materials was investigated at the low-field-side (outer) strike-point area of the ASDEX Upgrade (AUG) divertor during H-mode discharges with small and frequent ELMs. To this end, Au and Mo marker samples with different surface morphologies and geometries were exposed to plasmas using the DIM-II divertor manipulator. The results were compared to existing erosion and deposition patterns from various L- and H-mode experiments, in the latter case the main difference was the size and frequency of the ELMs.We noticed that increasing surface roughness reduces net erosion but less than what is the case in L-mode. On the other hand, net-erosion rates in H-mode are generally 2–5 times higher than the corresponding L-mode values, in addition to which exposure in H-mode conditions results in strong local variations in the poloidal and toroidal erosion/deposition profiles. The latter observation we associate with the large migration length, on the order of several cm, of the eroded material, resulting in strong competition between erosion and re-deposition processes especially at poloidal distances > 50 mm from the strike point. Considerable net erosion was measured throughout the analysed poloidal region unlike in L-mode where the main erosion peak occurs in the vicinity of the strike point. We attribute this qualitative difference to the slow decay lengths of the plasma flux and electron temperature in the applied H-mode scenario.Both erosion and deposition require detailed analyses at the microscopic scale and the deposition patterns may be drastically different for heavy and light impurities. Generally, the rougher the surface the more material will accumulate on locally shadowed regions behind protruding surface features. However, rough surfaces also exhibit more non-uniformities in the quality or even integrity of marker coatings produced on them, thus complicating the analyses of the experimental data.We conclude that local plasma parameters have a huge impact on the PFC erosion rates and, besides incident plasma flux, surface morphology and its temporal evolution have to be taken into account for quantitative estimates of erosion rates and PFC lifetime under reactor-relevant conditions.